2020
DOI: 10.1111/micc.12614
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual microcirculation in prehospital critical care medicine: A proof‐of‐concept study

Abstract: ObjectiveDiagnostic and risk stratification are limited in emergencies. The measurement of microcirculation might identify patients with poor perfusion but compensated macrocirculation such as in beginning shock. This proof‐of‐concept study examines whether sublingual prehospital sidestream dark‐field microscopy is feasible.MethodsThis prospective observational study included patients receiving medical aid by an emergency ambulance who had a spontaneous circulation and offered access to the sublingual mucosa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…There is still controversy about the interpretation of the data from this study [35]. Another promising approach is the investigation of sublingual microcirculation using Sidestream Dark Field Imaging (SDF) [36]. In the early stages of shock, there is currently no clear benefit for SDF [37].…”
Section: Discussionmentioning
confidence: 97%
“…There is still controversy about the interpretation of the data from this study [35]. Another promising approach is the investigation of sublingual microcirculation using Sidestream Dark Field Imaging (SDF) [36]. In the early stages of shock, there is currently no clear benefit for SDF [37].…”
Section: Discussionmentioning
confidence: 97%
“…One possibility would be to directly assess the microcirculation to detect disturbed organ perfusion, which could detect organ function failure at an early stage, and to treat this earlier [31,32]. A commonly investigated method for direct microcirculation measurement is the use of hand-held-video microscopy, which is mainly used sublingually [33], and can be used for example even in the context of emergency medical situations [34]. In the context of the COVID-19 pandemic, the important role of microcirculation in this disease has been analyzed several times [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…[56,57] Numerous studies have shown that alterations in the sublingual microcirculation can surpass alterations in systemic hemodynamic parameters in terms of their predictive accuracy. [58] In a severely infected porcine model, the OPS technique revealed major alterations in both sublingual and intestinal microcirculation. [59] The microcirculatory changes were correlated with the severity of the infection.…”
Section: Scorementioning
confidence: 99%